PRODUK PEMBIAYAAN PADA LEMBAGA KEUANGAN SYARI’AH: Produk, Pembiayaan, Lembaga Keuangan, Syari’ah - Sufyan Sufyan (Risâlah, Jurnal Pendidikan dan Studi Islam, 2020)
Abstract This article is structured to present financing products to Islamic financial institutions. The method used in this study is based on library data. Therefore, this research is called qualitative research in the form of library research that uses literature as the main object as a reference for study material. The results show that there are three products and services offered in Islamic banking. These three products are fund raising products, fund distribution products, and service products. While for self-financing can be done with the principles for results, leases, buying and selling and through a complementary contract.